2023
DOI: 10.1002/mnfr.202300015
|View full text |Cite
|
Sign up to set email alerts
|

Reshaped Gut Microbial Composition and Functions Associated with the Antifatigue Effect of Salidroside in Exercise Mice

Abstract: Scope Salidroside (SA) is an active compound derived from Rhodiola rosea and is widely used in healthcare foods. However, the underlying mechanism and its specific role in regulating the gut microbial community during exercise (Ex) remains unknown. Methods and results Mice are subjected to a weight‐loaded swimming test (WST) Ex to determine how gut microbiota affects the antifatigue activity of SA. The SA‐treated group mice (100 mg kg−1.bw.) display a significant increase in swimming time compared to the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The microbial DNA was extracted using a Genomic DNA Kit, as previously stated. 25,26 16S rDNA gene sequencing (V3-V4 regions) was detected and amplified from the whole genome using the barcoded 338F/806R primer pair. All the amplicons were purified, quantified, and finally sequenced on an Illumina NovaSeq (CA, USA).…”
Section: S Rdna Analysis Of Gut Microbiotamentioning
confidence: 99%
“…The microbial DNA was extracted using a Genomic DNA Kit, as previously stated. 25,26 16S rDNA gene sequencing (V3-V4 regions) was detected and amplified from the whole genome using the barcoded 338F/806R primer pair. All the amplicons were purified, quantified, and finally sequenced on an Illumina NovaSeq (CA, USA).…”
Section: S Rdna Analysis Of Gut Microbiotamentioning
confidence: 99%
“…The microbial DNA was extracted from the colonic contents of the mice using the Genomic DNA Kit (Omega Bio-Tek) in a sterile environment with promptness. As previously stated, [23] the 16S rRNA gene sequencing (V3-V4 regions) was to detect only bacteria, amplified from the whole genome using barcoded 341F/806R primer pair (341 F, 5′-CCTAYGGGRBGCASCAG-3′ and 806 R, 5′-GGACTACHVGGGTWTCTAAT-3′). The PCR conditions were set as 95 °C for 5 min, followed by thirty cycles at 95 °C for 30 s, 60 °C for 30 s, 75 °C for 30 s, and a final extension of 75 °C for 10 min.…”
Section: S Rrna Analysis Of Gut Microbiotamentioning
confidence: 99%
“…It was notable that 20 mg/kg/day salidroside administration remarkably enhanced the abundance of phyla Verrucomicrobia suppressed by LPS and reduced the abundance of phyla Proteobacteria promoted by LPS. Experiments administering salidroside (100 mg/kg/day) to mice for 4 weeks revealed that salidroside increased the relative abundance of beneficial microbes: Alistipes, Rikenellaceae, Parabacteroides, and Lactobacillus , while decreasing the relative abundance of harmful bacteria such as Candidatus Arthromitus ( Zhu et al, 2023 ). Wang et al sought to determine whether salidroside could mitigate the symptoms of colitis induced by dextran sulfate sodium (DSS)-induced colitis ( Wang et al, 2021 ).…”
Section: Salidroside and Gut Microbiotamentioning
confidence: 99%